Enzymatic Degradation of Cellulosic Fibers by Trichoderma Reesei Cellulase - Marie-Alice, ROUSSELLE; MIZUTANI, Chiyomi (Sen'i Kikai Gakkaishi (Journal of the Textile Machinery Society of Japan), 2001)
The hydrolysis of native cellulose by cellulase has been studied from the view point of synergistic action of three cellulase component, endocellulase (1, 4 -β-D-glucan 4 -glucanohydrolases), exocellulase (1, 4-β-D-glucan cellobiohydrolases) and β-glucosidase. We have attempted a separation of the commercial Trichoderma reeseicellulase by means of chromatography to enable us to measure enzymatic characteristics. Cellulosic fibers such as cotton, Tencel and viscose rayon and so on were used as the substrate for treatment by Trichoderma reeseicellulase to evaluate physical properties. Results from this work include : 1) Trichoderma reeseicellulase is rich in endocellulase after separation by chromatography. 2) Characteristic changes of cellulosic fibers after enzyme treatment were measured, including weight loss and reducing sugar with increasing incubation time. However, crystalline structure of cellulosic fibers has not changed after treatment. Degree of polymerization and that of crystallinity of cellulosic fibers except Tencel have changed slightly.